2018
DOI: 10.5213/inj.1836064.032
|View full text |Cite
|
Sign up to set email alerts
|

Add-on Therapy With the α-Blockers Tamsulosin and Naftopidil Improves Voiding Function by Enhancing Neuronal Activity in Prostatic Hyperplasia Rats

Abstract: PurposeBenign prostatic hyperplasia (BPH) impacts quality of life in men by causing lower urinary tract symptoms. α1-Adrenoceptor (α1-AR) blockers improve lower urinary tract symptoms. We investigated the efficacy of add-on therapy with α1-AR blockers on BPH rats.MethodsRats in the drug-treated groups were orally administered each drug once a day for 30 days after orchiectomy. To induce BPH, rats were castrated and testosterone (20 mg/kg) was injected subcutaneously once per day for 30 days. Cystometry was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…First, this cross-sectional study could not be used to infer causality. Second, we could not adjust genetics and inflammations components as risk factors, both of which are one of important risk factors [ 8 ]. Additionally, this study might have a potential selection bias because we used a single institutional data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this cross-sectional study could not be used to infer causality. Second, we could not adjust genetics and inflammations components as risk factors, both of which are one of important risk factors [ 8 ]. Additionally, this study might have a potential selection bias because we used a single institutional data.…”
Section: Discussionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH) refers to voiding dysfunction resulting from prostate enlargement and bladder outlet obstruction [ 7 ]. BPH is caused by nonmalignant, unregulated growth of the prostate gland, and it is a major cause of lower urinary tract symptoms (LUTS) [ 8 ]. BPH is highly prevalent in older men, and the prevalence was 27.7% according to a community-based study [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since alpha-1 adrenoceptors play an essential role in controlling the function of smooth muscles in the prostate and lower urinary tract, one of the most effective agents used to treat BPH and urological symptoms is the α 1 -adrenoceptor antagonist (alpha-1 blocker). Previous investigation showed that alpha-1 blockers were able to relax isolated prostate contraction in mice [39][40] and rats [41]. Therefore, agents which are able to relax the tone of rodent prostate smooth muscles via the same mechanisms as found in the human prostate, may relieve BPH symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The voiding function was evaluated by cystometry 18 days after the surgery, as previously described [15]. The rats were anesthetized with Zoletil 50 (10 mg/kg, intraperitoneally; Vibac Laboratories, Carros, France).…”
Section: Cystometrymentioning
confidence: 99%
“…Immediately after the cystometry, experimental animals were sacrificed for tissue collection. Tissue preparations were performed as previously described [15,16]. The rats were anesthetized using Zoletil 50 (10 mg/kg, interperitoneally; Virbac Lab-oratories).…”
Section: Tissue Preparationmentioning
confidence: 99%